Evaluating User Class Approach for Network Mobility Protoco - Md. Noor, Rafidah; Edwards, Christopher (Malaysian Journal of Computer Science, 2011)
This paper highlights the importance of the Quality of Service in mobile network by introducing a user class approach for traffic management between a mobile router and the mobile network nodes. The approach scheme encompasses the application of mobile user (e.g. public transport user) while they are moving to optimize the network resource utilization. Experiments are conducted using a Network Simulator 2 to measure the performance of user class in different scenarios; off peak hours and peak hours. Based on this information, traffic from mobile network nodes has significant improvement where it provides high throughput, low end-to-end delay and low packet loss rate.